Evaluation of the Flexural Strength Values of Acrylic Resin Denture Bases Reinforced with Silicon Dioxide Nanoparticles: A Systematic Review and Meta-analysis - Asal Moravej; Mahtab Salehi; Ali Salehi; Armin Khosravi; Kavan Yaghmoori; Farnaz Rezvan (International Journal of Scientific Research in Dental and Medical Sciences (IJSRDMS), 2023)
Background and aim: In the present study, differences in the effects of adding SiNPs at different concentrations (1wt%, 3wt%, 5wt%, and 7wt%) on the flexural strength of the heat-polymerized PMMA were investigated.Material and methods: Based on the PRISMA 2020 Checklist, the current study is a systematic review and meta-analysis. Databases from Scopus, Science Direct, PubMed, ISI, Web of Knowledge, and Embase were searched until 12 December 2022 to find systematic literature. The 95% confidence interval for mean differences was calculated using the fixed effect model and inverse-variance method. Stata/MP. v.17 software was used to conduct the meta-analysis.Results: Duplicate studies were removed from the initial review, which also reviewed 97 studies' abstracts. Two authors thoroughly reviewed 39 studies, and six studies were finally selected. Mean differences of flexural strength between the addition of 1%, 3%, 5%, and 7% SiNPs reinforcement and control group was 12.99 (MD, 12.99 95% CI 9.92, 16.05; p>0.05), 5.94 (MD, 5.94 95% CI 4.98, 6.91; p>0.05), 8.28 (MD, 8.28 95% CI 7.14, 9.43; p>0.05) and -2.97 (MD, -2.97 95% CI -3.87, -2.07; p>0.05), respectively.Conclusions: Based on the present meta-analysis, no statistically significant difference was observed between the effects of adding SiO2 nanoparticles at different concentrations (1wt%, 3wt%, 5wt%, and 7wt%) on flexural strength of the heat-polymerized acrylic compared to the control group. No specific concentration of SiO2 nanoparticles is suitable for strengthening acrylic resin.